Dementia patient care centre system, Android application for person-centered care, PEAR front end system - Teo, Kok Sang (2016)
With a global aging population, dementia sufferers are expected to increase in the next half century. There is no cure to dementia condition as of today and this has sparked motivation for researchers around the world to bring about a breakthrough in treatment in time to come. There is a need for coordinated effort to track the evolution of the disease, create policies to address the impact of dementia and lastly to conduct treatment and having effective care for existing dementia patients. Study has shown that person-centered care is proven to improve patient’s dementia condition by providing caregiver support and family experience. Person-centered care considers the individual’s unique abilities, interests, preferences and needs as compared to medicinal treatment that considers symptoms and behaviours. However due to the lack of resources, it is a big challenge for healthcare providers to provide such treatment. This project aims to improve the efficiency outputs of person-centered care centres with the implementation of Information Technology (IT), specifically on the front end system named PEAR which interacts directly with the patient and working personnel. Using the User Interface (UI) design done up by the predecessor of the project Sutrisno Suryajava Dwi Putra as reference, the author continues to further develop new functionalities such as creating an interface for patient’s to have their own photo album and a game interface which relates to the list of assigned games for patient’s as well as providing dynamic database entries into the backend of the system. The author also works closely together with his teammate Keith Tay Tat Leong in developing other aspects of the front end of the system such as app notification and other functionality. PEAR was developed with maintainability, flexibility and user experience as the main focus as stated in the predecessor’s notes and written documents. The author believes that with the continuous development of the system, it will then provide better efficiency outputs of person-centered care. The author also believes that the project will be easily handed over to the new FYP students to improve on the system outputs.